2023
DOI: 10.1186/s12887-023-04122-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for thrombosis in children and newborns: systematic evaluation and meta-analysis

Abstract: Background Thrombosis is a serious condition in children and neonates. However, the risk factors for thrombosis have not been conclusively determined. This study aimed to identify the risk factors for thrombosis in children and neonates in Intensive Care Unit (ICU) through a meta-analysis to better guide clinical treatment. Methods A systematic search of electronic databases (PubMed, Embase, Cochrane Library, WOS, CNKI, Wanfang, VIP) was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…According to studies conducted in Canada, Germany, and Denmark, the incidence of thrombosis among newborns is approximately 2.4/1000 children in ICU and 5.5/100,000 births in general. The meta-analysis summarizing the incidence of thrombosis in ICU children found that the incidence rate of ICU thrombosis is approximately 2%, which is consistent with previous studies [8].…”
Section: Neonatal Hemostasis System Peculiarities and Neonatal Thromb...supporting
confidence: 90%
“…According to studies conducted in Canada, Germany, and Denmark, the incidence of thrombosis among newborns is approximately 2.4/1000 children in ICU and 5.5/100,000 births in general. The meta-analysis summarizing the incidence of thrombosis in ICU children found that the incidence rate of ICU thrombosis is approximately 2%, which is consistent with previous studies [8].…”
Section: Neonatal Hemostasis System Peculiarities and Neonatal Thromb...supporting
confidence: 90%